Explanatory factors of acquiring English oral comprehension skills in secondary education: a comparison between Spain and The Netherlands - González Villarón, María; Egido Gálvez, Inmaculada (Revista Complutense de Educación, 2016)
Based on the current relevance of foreign language education and acquisition, this article presents a statistical analysis of the data provided by Spain and The Netherlands from the First European Survey on Language Competences (ESLC) (European Commission, 2012a). The intention of the statistical analysis of this data is to shed light on two main issues. First, it offers a description of student performance in both countries, regarding oral comprehension in English at the end of the stage of compulsory secondary education. Secondly, it delves into potential explanatory factors of performance in English in this evaluated skill area in both contexts, analyzing the influence which certain variables, related to students’ own characteristics, family and school environment, reveal. The article’s final aim, based on the conclusions, is to propose ideas for reflection, thought and improvement in the teaching and learning of foreign languages in Spain, particularly in the area of oral comprehension. The article concludes with the necessity to understand how some factors which are not directly related to the school system determine, to some extent, the success of the implementation of the diverse initiatives in the field of second language acquisition. In this sense, ESLC analysis highlights the incidence of various elements in the process of learning a foreign language.